Perceived Retail Crowding and Shopping Satisfaction: What Modifies This Relationship? - Machleit, Karen A.; Eroglu, Sevgin A.; Mantel, Susan Powell (Journal of Consumer Psychology, 2000)
Research has shown that an increase in perceived crowding in a retail store (created from either human or spatial density) can decrease the level of satisfaction that shoppers have with the store. The three studies reported here examine the retail crowding‐satisfaction relationship to determine the extent to which it is a simple, direct relationship. Specifically, we consider the possibility that the crowding–satisfaction relationship is mediated by emotional reactions that are experienced while shopping. In addition, moderating variables such as prior expectations of crowding, tolerance for crowding, and store type are examined for their influence on the crowding–satisfaction relationship. The results of two field studies indicate that whereas emotions only partially mediate the relationship, the decrease in shopping satisfaction due to crowding is moderated by expectations of crowding and personal tolerance for crowding. A laboratory experiment replicated the field studies and shows, in addition, that although ceiling and floor effects may be present, the relationship between perceived crowding and shopping satisfaction appears to vary by store type.